Mid-term results of revision total hip arthroplasty using the oval-shaped uncemented Trč-Cingr cup - Šťastný, Eduard; Trč, Tomáš; Handl, Milan; Kos, Petr; Kautzner, Jakub; Philippou, Theodoros; Lisý, Jiří (International orthopaedics, 2014)
PURPOSE: The aim of the present study was to introduce a novel oblong revision cup type TC for use in revision total hip arthroplasty (THA), and to evaluate mid-term results in terms of bone tissue remodelling in the immediate area of the implant. METHODS: The results of 31 patients that underwent revision THA between 2004 and 2008 are presented. The mean follow-up interval was 7.1 years (range 5.3-9.3 years, minimum of five years following revision). Osteointegration of the implant and bone tissue remodelling around the implant and ribs were assessed by X-ray and computed tomography (CT). RESULTS: The average Harris hip score increased from 39.8 to 85.3. Excellent results were achieved in nine patients, good in 16, fair in three and poor in three. According to X-ray results, 25 hips had a well-fixed, bone-ingrown cup and five had a stable fibrous union in the middle and the distal third of the implant. Proximal migration of the cup was noted in one case. Pelvic CT was additionally performed in ten patients. In all cases, we detected bone remodelling in the space between the implant ribs. Kaplan-Maier survivorship of the acetabular components was 94.2 % at 7.1 years. CONCLUSIONS: Our results show that the novel oblong revision cup type TC is relatively simple to implant, and is associated with reliable primary fixation and documented osteointegration and bone remodelling in the immediate area.
Keywords: senioři; náhrada kyčelního kloubu; Prosthesis Design; senioři nad 80 let; reoperace; Arthroplasty, Replacement, Hip; Time Factors; výsledek terapie; Middle Aged; mužské pohlaví; kyčelní protézy; Adult; Reoperation; protézy - design; Aged, 80 and over; ženské pohlaví; Humans; časové faktory; lidé středního věku; Hip Prosthesis; dospělí; Female; Aged; Treatment Outcome; lidé; Male